Cancer antigen-125 and risk of atrial fibrillation: a systematic review and meta-analysis. Issue 1 (7th January 2018) - Cheung, Angel; Gong, Mengqi; Bellanti, Roberto; Ali-Hasan-Al-Saegh, Sadeq; Li, Guangping; Roig, Eulàlia; Núñez, Julio; Stamos, Thomas D; Yilmaz, Mehmet Birhan; Hakki, Kaya; Wu, William K K; Wong, Sunny Hei; et al.
Abstract : Background: Cancer antigen-125 (Ca-125) is traditionally recognised as a tumour marker and its role in cardiovascular diseases has been studied only in recent years. Whether Ca-125 is elevated in patients with atrial fibrillation (AF) and its levels predict the risk of AF remains controversial. Therefore, we conducted a systematic review and meta-analysis of the association between Ca-125 levels and AF. Methods: PubMed and EMBASE databases were searched until 1 June 2017 for studies that evaluated the association between Ca-125 and AF. Inclusion criteria included studies that compare Ca-125 in patients with and without AF, or those reporting HRs/ORs for risk of AF stratified by Ca-125 levels. Results: A total of 39 entries were retrieved from the databases, of which 10 studies were included in the final meta-analysis. Ca-125 was significantly higher in patients with AF compared with those in sinus rhythm (mean difference=16 U/mL, 95% CI 2 to 30 U/mL, P<0.05; I 2 : 98%). Ca-125 significantly increased the risk of AF (HR: 1.39, 95% CI 1.06 to 1.82, P<0.05; I 2 : 84%). Conclusion: Ca-125 was significantly higher in patients with AF than in those in sinus rhythm, and high Ca-125 is predictive of AF occurrence. However, the high heterogeneity observed means there is an uncertainty in the relationship between Ca-125 and AF, which needs to be confirmed by larger prospective studies.